A randomized phase II study to determine the efficacy and tolerability of two doses of eribulin plus lapatinib in trastuzumab-pretreated patients with HER-2-positive metastatic breast cancer (E-VITA). Issue 4 (April 2019) - Bischoff, Joachim; Barinoff, Jana; Mundhenke, Christoph; Bauerschlag, Dirk O.; Costa, Serban-Dan; Herr, Daniel; Lübbe, Kristina; Marmé, Frederik; Maass, Nicolai; von Minckwitz, Gunter; Grischke, Eva-Maria; Müller, Volkmar; et al.
Abstract : The E-VITA study evaluated the efficacy and tolerability of two schedules of eribulin and lapatinib in patients with trastuzumab-pretreated HER-2-positive metastatic breast cancer. This multicenter, open-label phase II trial, randomly assigned patients with trastuzumab-pretreated HER-2-positive metastatic breast cancer to lapatinib 1000 mg daily with eribulin 1.23 mg/m 2 (equivalent to 1.4 mg/m 2 eribulin mesylate) days 1+8 every 21 days (split-dose arm) or eribulin 1.76 mg/m 2 (equivalent to 2.0 mg/m 2 eribulin mesylate) day 1 every 21 days (3-weekly arm). Time to progression and tolerability were defined as primary end points; no sample size calculation for formal comparison of efficacy data has been performed. Secondary end points included objective response rate, clinical benefit rate, and overall survival. Overall, 43 patients of a planned number of 80 patients were recruited. At a median follow-up of 28.7 months, the median time to progression was 8.1 months [95% confidence interval (CI): 4.8–9.4] in the split-dose arm and 6.5 months (95% CI: 4.6–13.4) in the 3-weekly arm. Objective response rate was 52.4% (95% CI: 31.0–73.7) in the split-dose arm and 45.0% (95% CI: 23.2–66.8) in the 3-weekly arm, and clinical benefit rate was 71.4% (95% CI: 52.1–90.8) and 75.0% (95% CI: 56.0–94.0), respectively. Overall survival was also similar in both arms. The most frequent grade 3–4 adverse events were neutropenia (58.5%) and leukopenia (39.0%). The combination of eribulin and lapatinib showed an acceptable safety profile with less toxicity observed in the eribulin 1.23 mg/m 2 day 1+8 group. This might be an alternative regimen when other treatment options are exhausted. Therefore, further clinical studies are warranted.